The Influence of Oybek’s Father on His Life and Literary Career - Ubaydullaev Zikrilla (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Oybek, one of Uzbekistan’s most celebrated writers, was deeply influenced by the wisdom, values, and intellectual guidance of his father. From an early age, his father instilled in him a love for literature, education, and cultural heritage, shaping his literary and ideological outlook. This influence is evident in Oybek’s works, which emphasize themes of justice, perseverance, and national identity. His father’s moral teachings and encouragement of intellectual curiosity played a crucial role in Oybek’s development as a writer, enabling him to balance tradition and modernity. Through an analysis of Oybek’s life and literary contributions, this study highlights the enduring impact of parental influence on creative expression and cultural preservation.